In vivo RNAi screen identifies candidate signaling genes required for collective cell migration in Drosophila ovary. - Luo, J.; Zuo, J.; Wu, J.; Wan, P.; Kang, D.; Xiang, C.; Zhu, H.; Chen, J. (Science China. Life sciences, 2015)
Collective migration of loosely or closely associated cell groups is prevalent in animal development, physiological events, and cancer metastasis. However, our understanding of the mechanisms of collective cell migration is incomplete. Drosophila border cells provide a powerful in vivo genetic model to study collective migration and identify essential genes for this process. Using border cell-specific RNAi-silencing in Drosophila, we knocked down 360 conserved signaling transduction genes in adult flies to identify essential pathways and genes for border cell migration. We uncovered a plethora of signaling genes, a large proportion of which had not been reported for border cells, including Rack1 (Receptor of activated C kinase) and brk (brinker), mad (mother against dpp), and sax (saxophone), which encode three components of TGF-? signaling. The RNAi knock down phenotype was validated by clonal analysis of Rack1 mutants. Our data suggest that inhibition of Src activity by Rack1 may be important for border cell migration and cluster cohesion maintenance. Lastly, results from our screen not only would shed light on signaling pathways involved in collective migration during embryogenesis and organogenesis in general, but also could help our understanding for the functions of conserved human genes involved in cancer metastasis.